2017
DOI: 10.1016/j.bbmt.2017.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Autologous Hematopoietic Cell Transplantation in Adult Patients with Acute Myeloid Leukemia: Who May Benefit from Autologous Hematopoietic Cell Transplantation?

Abstract: The role of autologous hematopoietic cell transplantation (auto-HCT) for postremission therapy of acute myeloid leukemia is yet to be elucidated. We retrospectively analyzed 240 patients treated with auto-HCT in first remission. All patients were treated with standard induction chemotherapy, and CD34 stem cells were collected at each cycle of consolidation. Stem cells were infused after total body irradiation (1200 cGy), cytarabine (9 g/m), and melphalan (100 mg/m). Estimated 5-year overall survival, disease-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
(57 reference statements)
2
12
0
Order By: Relevance
“…Similarly, Qin et al [41] reported that a CBFB/MYH11 level of >.2% after 2 courses of consolidation was an independent prognostic factor for poor OS, DFS, and cumulative incidence of relapse in autografted patients. High expression of Wilms' tumor gene 1 (WT1) in leukapheresis of peripheral blood autografts pre-ASCT has been associated with a high risk of relapse (cutoff value for WT1: 80 copies/10 4 ABL; 87% versus 30%; P = .0001) [53], consistent with the results published by Yoon et al [21]. In addition, Mule et al [54] reported that individualized MRD parameters, combined with WT1 and other non-leukemia-specific genes, such as PRAME and MSLN, can predict prognosis after ASCT in patients with AML with high sensitivity.…”
Section: Minimal Residual Disease Status Pre-asctsupporting
confidence: 85%
See 3 more Smart Citations
“…Similarly, Qin et al [41] reported that a CBFB/MYH11 level of >.2% after 2 courses of consolidation was an independent prognostic factor for poor OS, DFS, and cumulative incidence of relapse in autografted patients. High expression of Wilms' tumor gene 1 (WT1) in leukapheresis of peripheral blood autografts pre-ASCT has been associated with a high risk of relapse (cutoff value for WT1: 80 copies/10 4 ABL; 87% versus 30%; P = .0001) [53], consistent with the results published by Yoon et al [21]. In addition, Mule et al [54] reported that individualized MRD parameters, combined with WT1 and other non-leukemia-specific genes, such as PRAME and MSLN, can predict prognosis after ASCT in patients with AML with high sensitivity.…”
Section: Minimal Residual Disease Status Pre-asctsupporting
confidence: 85%
“…Multivariate analysis identified risk stratification as an important prognostic factor for both OS and LFS after ASCT. Yoon et al [21] reported similar outcomes in 240 patients with AML in CR1 who underwent ASCT following a conditioning regimen including total body irradiation (TBI; 1200 cGy), cytarabine (9 g/m 2 ), and melphalan (100 mg/m 2 ); OS decreased as the cytogenetic risk increased at 5 years after ASCT, with the highest 5-year OS in 19 patients carrying t(8;21) with isolated Y chromosome loss. In a previous study, we identified cytogenetic risk as an independent prognostic factor for survival outcomes, with decreasing OS and DFS as risk increased [18].…”
Section: Cytogenetic and Molecular Risk Stratificationmentioning
confidence: 92%
See 2 more Smart Citations
“…For patients in CR, we searched for available donors for allogeneic-hematopoietic cell transplantation (HCT) during the consolidation period, giving initial preference to human leukocyte antigen (HLA)-matched sibling donors (MSDs), followed by HLA well-matched unrelated donors (URDs). When conventional donors were not available, we searched for haploidentical familial mismatched donors; if a patient refused allogeneic-HCT, we performed autologous-HCT or completed three cycles of consolidation chemotherapy alone according to the patient's and physician's joint decision [ 16 17 18 ]. If a patient was a candidate for autologous-HCT, CD34+ hematopoietic stem cells were collected for 3 days during consolidation chemotherapy after the neutrophil count had recovered.…”
Section: Methodsmentioning
confidence: 99%